A importância da proeminência da frase fonológica no português brasileiro (Revista de Estudos da Linguagem, 2004)
In order to show the importance of phonological phraseproeminence in Brazilian Portuguese, we make an intonationalanalysis of contexts which characterize vowel merge and voweldeletion processes. We will argue that this phonologicalproeminence blocks vowel sandhi processes because it carries thesyntactic notion of recursivity in Portuguese. The results contributeto syntax-phonology interface discussion.